Timah Hitam (Pb) dan Karies Gigi - Anita Dewi Moelyaningrum (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Environmental polution had many impact for health. Lead (Pb) had been found in the environmental like in the air, land and water. The source of the lead pollution were smoke of transportation, paint, pipes, waste and industries. Dental carries is tooth decay or breakdown the tooth bone. Lead (Pb) in the body was predicted causes the dental carries. The aim of the research is analysis the correlation between the lead (Pb) and dental carries from journals and literatures.  The result. Epidemiological study showed that lead (Pb) exposure increase the risk of dental carries. The animal research showed that lead (Pb) disturbing elements in the body. Lead (Pb) inhibits the calcium absorbtion which it was needed to form the tooth and saliva glands. So it increased the risk of dental carries. Blood lead level (BLL) increase the risk of dental carries. Conclution. The lead (Pb) Exposure increase the dental carries. The lead (Pb) pollutin in the environment should be controlled to protect the healthy tooth.